γ-tocopherol methyltransferase gene sequencing and SNP discovery associated with olive oil quality: SNP discovery associated with tocopherol level in olive oil - Ayadi, Nadia; Rayda Ben Ayed,; Ercisli, Sezai; Durul, Melekber Sulusoglu; Sakar, Ebru; Rebai, Ahmed (Cellular and Molecular Biology, 2023)
γ-tocophérol methyltransferase (GTMT), a key enzyme in the tocopherols biosynthesis pathway, is involved in the conversion of δ- and l'γ-tocophérol to β- et l'α-tocophérol, respectively. In fact, it plays an important role in the α-tocopherol composition and the quality of olive oil. A total of 14 olive tree cultivars (Olea Europaea L.) were chosen and used in this study. They were sampled from different regions of Tunisia. Four cultivars from four Mediterranean regions (Greece, Algeria, Morocco, and Spain) were included for comparison. For each variety, DNA was extracted from young leaves. The Vte4 gene was PCR amplified from the 14 olive varieties and verified by electrophoresis on a 2% agarose gel for each variety. DNA sequencing of the olive cultivars revealed several single-nucleotide polymorphisms (SNPs). Statistical and bioinformatics analysis draw attention to some associations between some of the SNPs, tocopherols contents and oleic acid content. In fact, two significant associations are obtained between SUBS24 and both Total-Tocopherols and Beta-Tocopherol. Moreover, dendrograms reveals that there is a correlation between genetic variability and chemical characteristics which make the Vte4 gene more interesting in terms of tocopherols levels.